Complex and Connected Lives: Voices of “English Language Learners” in Middle School - Anny F Case (Middle Grades Review, 2021)
In addition to the typical ups and downs of middle school (MS), English language learners (ELLs) in the middle grades also grapple with learning English, straddling multiple cultures, and adapting to the realities of immigration. While school systems tend to focus on linguistic and academic development, MS ELLs exercise agency, creativity, judgment, and resilience as they navigate hybrid identities, complex and context-specific social and cultural expectations, and home/school connections and disconnections. This article reports on an interview study of middle school ELLs from a variety of backgrounds. Using self-selected artifacts representing their in-school and out-of-school lives, participants discussed their in- and out-of-school lives, social networks, impressions of school, and goals for the future. Themes of navigating complexity and forging connection point to a portrait of middle school ELLs with initiative, purpose, and dimensionality that challenges the narrow focus on language often prominent in the professional discourse about ELLs.
Keywords: multilingual students; English language learners; middle school